Pendekatan Manajemen dalam Perencanaan Tenaga Pendidik pada Lembaga Pendidikan Islam: Management Approach in Educational Staff Planning at Islamic Educational Institutions - Farid, Miftah; Mulyawan Safwandy Nugraha; Nurachadijat, Kun; Rosadi, Adi (Sekolah Tinggi Agama Islam Kharisma Cicurug Sukabumi, 2025)
In the digital era, fostering student autonomy is crucial, particularly in traditional Islamic boarding schools (pesantren) that still rely on teacher-centered methods. This study explores the application of heutagogy in enhancing student independence at Riyadul Muta’amilin Pesantren, Cidahu, Sukabumi. Using a qualitative case study, data were gathered from 60 santri and several teachers through interviews, observations, and document analysis. Results show that heutagogy—via blended learning and digital tools encouraged students to learn independently. Learners showed greater enthusiasm, critical thinking, and reduced reliance on teachers. Teachers, in turn, used more flexible teaching strategies. The use of smartphones and educational software played a key role in promoting self-directed learning. This approach successfully bridges traditional and modern educational models in pesantren, fostering lifelong learning. Despite its promise, the study's findings are limited by its focus on one site and qualitative design. Further studies could broaden the scope or include quantitative methods for validation.